2020
DOI: 10.1182/blood.2020006520
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and coagulation: bleeding and thrombotic manifestations of SARS-CoV-2 infection

Abstract: Patients with coronavirus disease 2019 (COVID-19) have elevated D-dimer levels. Early reports describe high venous thromboembolism (VTE) and disseminated intravascular coagulation (DIC) rates, but data are limited. This multicenter, retrospective study described the rate and severity of hemostatic and thrombotic complications of 400 hospital-admitted COVID-19 patients (144 critically ill) primarily receiving standard-dose prophylactic anticoagulation. Coagulation and inflammatory parameters were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

89
1,284
29
64

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,169 publications
(1,466 citation statements)
references
References 22 publications
89
1,284
29
64
Order By: Relevance
“…In a study of 150 French ICU patients, only 4 (2.7%) were reported to have bleeding complications, which included intracerebral hemorrhage and extracorporeal circulation cannula hematoma 19 . In the Boston area study, the overall rate of hemorrhage was 4.8%, which was similar to the overall rate of VTE reported 7 . In a recent study from the United Kingdom of patients admitted to a critical care unit, 11% suffered from a major bleed 17 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In a study of 150 French ICU patients, only 4 (2.7%) were reported to have bleeding complications, which included intracerebral hemorrhage and extracorporeal circulation cannula hematoma 19 . In the Boston area study, the overall rate of hemorrhage was 4.8%, which was similar to the overall rate of VTE reported 7 . In a recent study from the United Kingdom of patients admitted to a critical care unit, 11% suffered from a major bleed 17 .…”
Section: Discussionmentioning
confidence: 75%
“…Laboratory monitoring of hospitalized patients with COVID‐19 provides a means to guide care but also may provide predictive and prognostic information. One of the most commonly reported abnormal laboratory findings in patients with COVID‐19 is highly elevated D‐dimer levels 3‐7 . Others include elevated fibrinogen, normal or mildly decreased platelets, and normal or near‐normal aPTT and PT 58‐60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Typhi infection has been reported to activate the coagulation system, increase serum brinogen and D-dimer and prolong PT and APTT [18]. COVID-19 infection may lead to disturbances in the procoagulation, anticoagulation and brinolytic systems [30][31][32][33][34]; a high concentration of D-dimer and prolonged PT are associated with severe COVID-19 and a poor prognosis [24]. In this study, we found that RBCs were detected in the stool of 2 patients, PT was prolonged and D-dimer was elevated in all 6 patients, while APTTs and brinogen levels were normal.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies used lower-extremity venous ultrasound scanning or CTPA to con rm the diagnosis of VTE only in the presence of a clinical suspicion, and we prede ned this study group as the "suspected screening group." [1,[3][4][5][6][8][9][10][11][12][13][14][15] Seven studies routinely screened VTE in every patient using lower-extremity venous ultrasound scanning, and this study group was prede ned as the "routine screening group." [16][17][18][19][20][21][22] Our primary aim was to determine the incidence of VTE in COVID-19 patients in two prede ned cohort subtypes:…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%